A Low-Temperature Solution-Process High-k Dielectric for High-Performance Flexible Organic Field-Effect Transistors - Mu, Qi; Chen, Zheng; Duan, Shuming; Zhang, Xiaotao; Ren, Xiaochen; Hu, Wenping (Frontiers in Materials, 2020)
Applying high-k dielectrics can effectively reduce the operating voltage of OFETs to a few volts, thus significantly miniaturizing the dynamic power consumption of OFETs. Aluminum oxide is known as a promising dielectric material for its high permittivity (k=6–9). In this work, a simple, low-cost, low-temperature (only 85 °C) solution process is used to prepare amorphous AlOx dielectric thin films for high-performance flexible OFET applications. The AlOx thin film was spin-coated and then solidified using deep ultraviolet irradiation without high-temperature annealing. The as-deposited AlOx thin film has a root mean square surface roughness of 0.47 nm and maintains a very low leakage current density of 8×10−9 A/cm2 at 3.5 MV/cm and high dielectric constant of about 8.3 (at 1 kHz). The complete OFET based on this dielectric can operate at a 3 V gate bias with saturation mobility of 1.8 cm2/Vs, and steep sub-threshold swing of 110 mV/dec. Our work demonstrated a low-temperature solution process to fabricate a high-k metal oxide dielectric for low-power OFET applications.